Pengaruh ammonia sebagai “killing agent” pada pengecatan bulu kulit kelinci - Bambang Oetojo; Muchtar Lutfi; Esti Rahayu (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1989)
The objective of this research is to find out the effluence of ammonium hydroxide as killing agent to the uniformity and fintness of the colour of rabbit fur after dyeing. This research made use of 27 pieces of green salted rabbit skin having white colour. In killing process the rabbit fur was treated recpectively in a liquar of 10, 15 and 20 cubic centimetres of ammonium hydroxide of 22% strength in one litre of water, furthermore the fur was dyed. The dyed fur was visually examined for the uniformity and fitness of the colour of the dyed fur, and physically tested for the rub fastness of the dye.The highest value of rub fastness achieved by the dyed rabbit fur treated in 20 cubic centimetres of ammonium hydroxide in one litre of water. It advisable to use 20 cubic centimetres of ammonium hydroxide of 22 % strength in one litre of water as killing agent in rabbit fur dyeng process.